The effect of consuming high levels of yogurt on sexual hormones and rates of gynecomastia in men of different ages - Omar Almuharib; Hussein Suhair Ali; Firas Najm Ismael (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Yogurt is one of the foods that receives wide attention in Iraqi society and has a high consumption rate at the per capita level because of its great benefits, the most important of which is as a source of calcium and its richness in other mineral elements, which made it a main meal for some. But despite the high benefits that yogurt provides, it causes health problems represented by high levels of calcium and iron, and being a mimic of estrogen (the female hormone), which causes a decrease in androgen levels in men, which causes a decrease in muscle mass, which is based on protein, and an increase in fat mass, which encourages the phenomenon of gynecomastia. In men, in addition to the high levels of insulin resistance in the body (type 2 diabetes) associated with hormonal activity. Methodology: The study includes 30 Persons with calculated ages:10 people (control)10 people between the ages of (20-30 years)10 people between the ages of (40-60 years)The study includes making apparent measurements (measuring gynecomastia) for people who consume yogurt daily in the areas of Ramadi .Doing hormonal tests:( LH - FSH - Prolactin - Testosterone - Estrogen) In addition to doing other tests (Zn - Ferritin - Ca) Result: the effect of excessive consumption of yogurt on a daily basis on some sexual hormones for men at different ages, as there was no significant difference in the LH hormone between the treatments and the control. 20-30 years old with 25 micro units / liter, while for people whose ages ranged between 40-60 years, its concentration was 29 micro units / liter compared to control 11 micro units / liter, while for testosterone in people who reached the age of 20-30 years it reached 193 micro units / liter and in people who reached the age of 40-60 years, its concentration was 150 micro units / liter compared to control 375 micro units / liter. Therefore, we conclude that drinking yogurt on a daily basis negatively affects sexual hormones for men.